2020
DOI: 10.3390/ph13110393
|View full text |Cite
|
Sign up to set email alerts
|

Potent Quinoline-Containing Combretastatin A-4 Analogues: Design, Synthesis, Antiproliferative, and Anti-Tubulin Activity

Abstract: A novel series of quinoline derivatives of combretastatin A-4 incorporating rigid hydrazone and a cyclic oxadiazole linkers were synthesized and have demonstrated potent tubulin polymerization inhibitory properties. Many of these novel derivatives have shown significant antiproliferative activities in the submicromolar range. The most potent compound, 19h, demonstrated superior IC50 values ranging from 0.02 to 0.04 µM against four cancer cell lines while maintaining low cytotoxicity in MCF-10A non-cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Unfortunately, the cis configuration of CA-4 has a propensity for undergoing transformation to the inactive trans configuration upon storage and during in vivo metabolism. To overcome this, many structural modifications of CA-4 have been undertaken where the cis double bond is replaced with heterocycles, either monocyclic, such as oxadiazole, isoxazole and imidazole, resulting in compounds, such as 1, 2 and 3 respectively (Figure 1) [27][28][29][30][31][32][33] or fused heterocyclic, such as pyrazolopyridines 34 , triazolopyridines 35 and triazolothiadiazine derivatives 36 . These compounds, like CA-4 showed pronounced activity against a panel of cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the cis configuration of CA-4 has a propensity for undergoing transformation to the inactive trans configuration upon storage and during in vivo metabolism. To overcome this, many structural modifications of CA-4 have been undertaken where the cis double bond is replaced with heterocycles, either monocyclic, such as oxadiazole, isoxazole and imidazole, resulting in compounds, such as 1, 2 and 3 respectively (Figure 1) [27][28][29][30][31][32][33] or fused heterocyclic, such as pyrazolopyridines 34 , triazolopyridines 35 and triazolothiadiazine derivatives 36 . These compounds, like CA-4 showed pronounced activity against a panel of cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…However, the poor hydrophilicity and BBB penetration ability of CA4 hampers its application in clinical (Gonawala et al, 2018). Therefore, numerous work about the design of CA4 derivatives has been done (Ibrahim et al, 2020;Romagnoli et al, 2018;Wang et al, 2019). To overcome these drawbacks of CA4, here, we design and synthesize a novel CA4 derivative (CA4D), which has a stable structure and physicochemical property.…”
Section: Introductionmentioning
confidence: 99%
“…Benzotriazole-based compounds are unique nitrogen-containing heterocycles that have attracted significant attention from medicinal chemists as a promising class of bioactive heterocyclic products that exhibit numerous biological properties, such as anticancer [ 27 , 28 , 29 , 30 , 31 ] (BZI, Figure 1 ), antibacterial [ 32 , 33 ], antiviral [ 34 , 35 ], and anti-inflammatory activities [ 36 , 37 ]. Furthermore, substitution of the 3,4,5-trimethoxyphenyl ring of isoCA-4 by a quinazoline nucleus [ 38 ] or quinoline [ 39 , 40 , 41 ] led to tubulin inhibitor with potent antiproliferative deeds versus a variety of cancerous cell lines. Recently, BZII with a benzotriazole moiety for the replacement for trimethoxyphenyl moiety of colchicine was reported ( Figure 1 ), and the docking studies of BZII showed that benzotriazole formed polar and hydrophobic interaction with the critical residue amino acids of α- and β-tubulin subunits in the colchicine-binding pocket.…”
Section: Introductionmentioning
confidence: 99%